The Influence of Psychology alienation in Student sociable accommodation (field study of families students out side the immigrate centers in Lattakia city) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
These research had shown, that Psychology alienation, which displaced families student suffered, cases by outside rezones as a result of changing there places , and movement from there home town to Lattakia city, where immigration cases some damages by student Psychology balance , so they becomes non sociable accommodation with society , so these research had done to search the rezones of naught ability of personage displaced families to sociable accommodation with society, and alienation filing , where research assured that no clear differences in the degree of alienation filing between men and women from personage displaced families, or according to study specialization , and also the research had shown that there are difference in the degree of alienation filing according to the age , where younger students had more alienation filing than the oldest , and these wont , that the elders students more ripen, and more open mind , and had more ability to understand the society changes , and more accommodation with society ,where they lives in.